Application value of CAIPIRINHA-VIBE with MOCO in liver magnetic resonance examination. Issue 140 (July 2021) - Hu, Junjiao; Xu, Bingren; Cao, Jinbo; Yang, Ru; Zhang, Huiting; Guo, Hu; Situ, Weijun; Liu, Jun
Highlights: This study explored the application of CAIPIRINA and MOCO techniques in liver VIBE sequence on 3.0 T MRI and found that these techniques had faster scanning time. The application of CAIPIRINA and MOCO techniques in liver VIBE sequence also improves image quality and reduces movement displacement. We discovered that the use of the new technique would provide is better imaging quality especially for patients in poor condition, who can't cooperate with breath-holding examination for a relatively long time resulting obvious motion artifacts in the image. Abstract: Objective: To compare the image quality of VIBE sequence using controlled aliasing in parallel imaging results in higher acceleration (CAIPIRINHA-VIBE) and using generalized autocalibrating partially parallel acquisitions (GRAPPA-VIBE) in liver magnetic resonance examination, and to evaluate the effect of non-rigid 3D-registration motion correction (MOCO) combined with CAIPIRINHA-VIBE on liver spatial location registration. Methods: A total of 85 patients underwent pre-contrast GRAPPA-VIBE and CAIPIRINHA-VIBE breath-hold scan in the mask phase, and then underwent CAIPIRINHA-VIBE breath-hold scan in arterial phase, portal vein phase and delay phase after administration. After the scanning of four phases of CAIPIRINHA-VIBE completed, 3D images without and with MOCO of each phase were automatically generated. The images quality of GRAPPA-VIBE and CAIPIRINHA-VIBE without MOCO in the mask phase was scored subjectively by two physicians. The number of slices at the top of the diaphragm in the arterial phase was taken as the base slice, and that in the other stages subtracted with the base slice for CAIPIRINHA without and with MOCO. The range of diaphragm movement in each phase was counted by + N/- N statistics. Results: The image quality and the scores of CAIPIRINHA-VIBE were significantly higher than those of GRAPPA-VIBE in respiratory motion artifact suppression, liver edge sharpness and intrahepatic vascular sharpness (p < 0.05). The spatial position consistency of the liver with MOCO is significantly better than that without MOCO. Conclusion: CAIPIRINHA-VIBE with MOCO can be used instead of conventional GRAPPA-VIBE sequence in upper abdominal MRI enhancement examination, especially for patients with poor breath-hold.